Bahasa dan Aksara Tafsir Al-Qur’an di Indonesia dari Tradisi, Hierarki hingga Kepentingan Pembaca - Islah Gusmian (TSAQAFAH, 2010)
This article demonstrates that a variety of local languages, like Javanese, Sundanese and Malay, have become a medium for writing Al-Qur’an commentaries in the archipelago. The choice of local languages for these texts is closely connected to the social-cultural circumstances where they were produced. For example commentaries in Malay Jawi appear in Aceh and Sumatra while commentaries in Javanese are found in the palaces and pesantren of Java. Moreover, the process of adoption and adaptation of Islam to local culture also characterized the dynamics of commentary writing in the region. Some commentators wrote in the Malay or Javanese language with an Arabic script and yet, while the influence of local cultures was so strong, other commentators used both the Arabic language.